Engineering for Rural Development 2019
DOI: 10.22616/erdev2019.18.n528
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable urban mobility planning development preconditions: governance system approach

Abstract: Sustainable mobility means keeping the ability of people to travel and supply goods in a way that balances environmental and socio-economic aspects and aims at the reducing of negative impacts on environment. The aim of this research is to study how the mobility governance is built and particularly governed in sustainability understanding aspects in urban municipalities in Latvia, using the case of Valmiera town. In the scope of this step-by-step complementary study different transportation modes have been stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is especially important given the Russian specifics described in the Literature Review section. The results obtained are consistent with the studies presented in the literature, which note that implementing innovation within the smart city concept is impossible without population participation, which is expressed in opinions, assessments, and suggestions [37][38][39][40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is especially important given the Russian specifics described in the Literature Review section. The results obtained are consistent with the studies presented in the literature, which note that implementing innovation within the smart city concept is impossible without population participation, which is expressed in opinions, assessments, and suggestions [37][38][39][40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 90%
“…At the same time, most researchers agree that implementing innovations within the concept of a smart city is impossible without the population's participation, which is expressed as opinions, assessments, and suggestions [37][38][39][40][41][42][43][44]. In examining the determinant factors affecting urban development, Myeong suggested that smart city development includes citizen participation with multi-communication channels in building a smart city.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mobility sharing makes it possible to meet the mobility needs of citizens and the supply of goods while ensuring positive impacts on the environment and promoting sustainable urban development [27].…”
Section: Role Of Car Sharing In Urban Sustainabilitymentioning
confidence: 99%
“…Regardless of the positive aspects of car-sharing and huge interest on the part of the environmentally aware population, it is still a niche. In Latvia, the phenomenon is less studied, and only some the authors are covering the topic to a limited extent [25][26][27][28]. Car sharing and environmentally friendly mobility in Latvia are relatively new concepts [26], and it is something that drivers use relatively rarely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation